The Impact of Foreign Investment on Balance of Payments Based on the Supply chain management: An Econometrics Study for the Period of 2005-2017 in Iraq - Alaa Abbas Dakhil; Maiami Salal Sahib Al-shukri; Mayih Shabeeb Al-Shammari (International Journal of Supply Chain Management, 2019)
This examination explores the effect of foreign direct investment on the supply chain management and balance of payment in Iraq market. The study is conducted in Iraqi circumstances focusing on the time period of 2005-2017 by considering the supply chain management. Johansen-Juselius co integration technique has been employed to measure the association among variables of interest which is FDI, CAB and GDP. In this context of particular importance are management concepts such as supply chain and chain quality management concepts. Therefore, our aim is to analyze the influence of Foreign Direct Investment (FDI) on the Iraq business. Furthermore, VECM estimation is carried out to determine a long and short run influence of FDI on current account balance. The results revealed that foreign investment is co-integrated with balance of payment. Furthermore, a positive impact of FDI has been recorded on CAB (current account balance). The results infer export led policy can positively affects the balance of payment with the foreign inflows. Therefore, as a policy implication, FDI should be taken into account when policy makers are making policies regarding economic development.